MENGENALKAN LITERASI DIGITAL PADA REMAJA: UPAYA PENCEGAHAN CYBERBULLYING DI ERA DIGITAL - Melda Rumia Rosmery Simorangkir (Universitas Bina Taruna Gorontalo, 2024)
Advancements in information and communication technology have facilitated boundless interactions between individuals across the globe, accelerated the flow of information, and simplified various economic activities. Education on safe and wise internet usage needs to be enhanced so that society can maximize the benefits of technology without facing detrimental risks. GPIB Marga Mulia Yogyakarta is concerned about the current situation among teenagers who are witnessing the prevalence of social media that portrays bullying as something amusing to the public. The enthusiasm and active participation of the participants during the PkM session indicate that this program is effective in capturing the attention of teenagers and raising their awareness about digital literacy and cyberbullying.